Ability of acanthamoeba cyst to excyst at different temperatures - Nurul Fariza Rossle,; Mohamed Kamel Abd Ghani,; Anisah Nordin,; Yusof Suboh,; Noraina Ab Rahim, (Penerbit UKM, 2011)
This study was carried out to observe thermotolerance ability of Acanthamoeba spp. A total of 32 Acanthamoeba spp. isolates obtained from water taps, sinks, swimming pools and sea water were used. Trophozoites of Acanthamoeba spp. were inoculated onto non-nutrient agar (NNA) seeded with heat-killed Escherichia coli using aseptic technique and incubated for 14 days at 30°C to obtain the cyst. The cysts were subcultured onto new agar plates for thermotolerance test at 37°C and 42°C. The plates were observed until 96 hours after incubation for excystation of Acanthamoeba before being declared negative. Overall, 81.25% of samples were able to excyst at 37°C while 37.5% were able to excyst at 42°C. Thermotolerant Acanthamoeba is associated with high pathogenicity potential.